2005
DOI: 10.1007/s10555-005-5050-6
|View full text |Cite
|
Sign up to set email alerts
|

Immunobiology of head and neck cancer

Abstract: The development of head and neck cancer (HNC) is strongly influenced by the host immune system. Recent evidence for the presence of functional defects and for apoptosis of tumor-infiltrating as well as circulating T cells in patients with HNC emphasizes the fact that their antitumor responses are compromised. It appears that H&N tumors not only effectively escape from the host immune system but also actively corrupt the host antitumor response via several distinct mechanisms. Strategies for restoring immune co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
126
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(130 citation statements)
references
References 24 publications
2
126
0
2
Order By: Relevance
“…23 Another caveat in interpreting our results is the immunosuppression that is characteristic of patients with advanced stages of head and neck cancer. 24 Although this may be a general characteristic of such patients, at least some of the subjects included in this study showed evidence of immune activity, including positive response to skin tests (7 of 21 patients) and high unstimulated lymphoproliferation (41000 c.p.m. ; 8 of 11 patients) ( Table 2 and clinical trial paper 8 ).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…23 Another caveat in interpreting our results is the immunosuppression that is characteristic of patients with advanced stages of head and neck cancer. 24 Although this may be a general characteristic of such patients, at least some of the subjects included in this study showed evidence of immune activity, including positive response to skin tests (7 of 21 patients) and high unstimulated lymphoproliferation (41000 c.p.m. ; 8 of 11 patients) ( Table 2 and clinical trial paper 8 ).…”
Section: Discussionmentioning
confidence: 79%
“…7 However, the use of the intratumoral route is complicated by the highly immunosuppressive microenvironment of the head and neck tumor. 24 Further studies must be conducted to determine whether presentation of tumor antigens by Hsp65 is required for its antitumoral effects or whether these effects are mediated by a reversion of immunosuppression mediated by the proinflammatory properties of this protein. If the latter is true, immunization away from the tumor (for example, skin at a distant site) may prove more efficient in achieving tumor regression by averting the effects of local immunosuppression.…”
Section: Discussionmentioning
confidence: 99%
“…5,16,17 On the other hand, tumors escape from immune surveillance by mechanisms such as down-modulation of HLA expression, mutation of these and other tumor antigens, the lack of costimulatory factors, production of immunosuppressive cytokines and apoptosis of effector T cells. 6 To generate tumor-specific T cells from PBMCs or TILs of patients with cancer, permanent tumor cell lines are usually established from tumor specimens. In general, tumor specimens from head and neck regions are difficult to propagate, and they are more often contaminated by bacteria, viruses, and mycoplasma due to their location, compared with the tumors from other locations.…”
Section: Discussionmentioning
confidence: 99%
“…Gun-1 cells were incubated with IFN-γ (100 IU/ml) for 48 h before being used as stimulators. Autologous MLTC was performed as follows: 2×10 6 PBMCs were stimulated with 2×10 5 MMC (kindly provided by Kyowa Hakko, Tokyo, Japan)-treated Gun-1 cells (100 µg/ml for 30 min at 37 °C). The cells were suspended in 2 ml AIM-V medium supplemented with 10% (v/v) heat-inactivated human AB serum, 20 IU/ml of IL-2 (kindly provided by Shionogi & Co., Ltd. Osaka, Japan), and 25 IU/ml of IL-4 (kindly provided by Ono Pharmaceutical Co., Ltd. Osaka, Japan).…”
Section: Mltc and The Establishment Of Cd4+ T Cell Clonementioning
confidence: 99%
See 1 more Smart Citation